Evaluation of Composting and the Quality of Compost from the Source Separated Municipal Solid Waste - D Dadi; H Sulaiman; S Leta (Journal of Applied Sciences and Environmental Management)
The aerobic composting potential and quality of Source Separated Municipal Solid Waste (SSMSW) was studied using four different treatments for over 80 days. Four different types of treatments using different inoculums were used for the composting of source separated municipal solid waste. The phytotoxicity tests of the different types of compost samples were conducted on 3 different types of seeds and 3 of the compost samples were rated very mature and only one of them is rated mature compost. The compost quality (physicochemical, nutrient composition & heavy or trace metal concentration of the matured composts) of the studied compost samples for all the treatments indicated that composting of SSMSW with cow dung is the best of all the treatments.